A review on sweet potato with special focus on Hungarian production II agronomy - Monostori Tamás (Review on agriculture and rural development, 2015)
Sweet potato [Ipomoea batatas (L.) Lam.], despite its tropical-subtropical origin, has successfully been grown for centuries also in temperate climate. Regarding the various aspects of agronomy, there are general rules that must be followed irrespective of the site of growing. These include the avoidance of forecrops promoting the accumulation of root-damaging pests and pathogens, as well as those increasing the risk of excessive N release; potassium-stressed nutrient supply; planting spacing in the 100 cm x 30 cm range; irrigation in the first 30-40 days; careful harvesting and post-harvest curing of storage roots, among others. Even these factors, however, must be adjusted to the conditions of the site of growing and, as far as possible, to the cultivars chosen. In our days in Hungary, cultivation methods based on international sweet potato literature or adapted from technologies of other crops of similar requirements are generally in use and continuously modified by individual experiences. The planning of scientifically recognized experiments for establishing site- and cultivar-specific approaches to all aspects of agronomy must consider all this information.